2013
DOI: 10.1590/s1414-462x2013000300005
|View full text |Cite
|
Sign up to set email alerts
|

Recusa familiar diante de um potencial doador de órgãos

Abstract: Objetivou-se analisar a recusa familiar diante de um potencial doador de órgãos e identificar seus motivadores através de relatos de familiares documentados em prontuários arquivados em um hospital de grande porte na cidade de Curitiba (PR), no ano de 2011. O método utilizado foi a pesquisa transversal do tipo qualitativa descritiva, com base na análise de conteúdo de Bardin. Emergiram dos relatos as categorias: discordância entre familiares; desconhecimento sobre a vontade do potencial doador; desejo de mante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
18

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 7 publications
1
6
0
18
Order By: Relevance
“…Contradicting the result of this study, the time to be entered on the death certificate refers to the time of BD characterization at the end of the BD determining process (11,14) . As the result of the donation, it appears the similarity with other studies conducted in Brazil on this theme, where we highlight the kidneys and corneas, respectively (2,16) . In these studies, no donation appears as predominant outcome.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Contradicting the result of this study, the time to be entered on the death certificate refers to the time of BD characterization at the end of the BD determining process (11,14) . As the result of the donation, it appears the similarity with other studies conducted in Brazil on this theme, where we highlight the kidneys and corneas, respectively (2,16) . In these studies, no donation appears as predominant outcome.…”
Section: Discussionsupporting
confidence: 83%
“…As for the distribution by age, it was found that the age range varied from 5 to 73 years, with a mean 42.3 years. These results are reinforced by the scientific literature, which shows that most PDs are young adults of working age (16)(17) . Thus, we consider our sample a group of heterogeneous people in age, since it involved from children to the elderly.…”
Section: Discussionmentioning
confidence: 61%
“…In most cases, family refusal is related to the lack of understanding of the diagnosis of BD, aspects related to religion and the unpreparedness of the professional who conducted the interview 26,27 . In other countries, such as the United States, family refusal is also related to other factors, such as doubts about the fairness of the distribution of organs through donation programs, with little representation of minorities, poor, disabled or elderly in the transplant lists 28 .…”
Section: Weaknesses In the Care For Potential Organ Donors: The Percementioning
confidence: 99%
“…A religiosidade e a cultura individual também se revelam como motivos para a não aceitação da manipulação do corpo, pois no imaginário dessas famílias, ao manuseá-lo, o mesmo perde sua integridade, ficando deformado e não sendo possível devolvê-lo como veio ao mundo 10 .…”
Section: Resumo | Introduçãounclassified
“…A família acredita que o empenho pela doação e os cuidados excessivos com o paciente, tem como objetivo a comercialização dos órgãos. Em alguns estudos, fica evidente nos relatos dos familiares o medo do tráfico de órgãos, que pode acontecer com seu ente querido, o que leva a pensar que a morte do paciente possa ser antecipada ou induzida para atender o interesse da equipe [10][11] . Incertezas desse tipo ocorrem quando os parentes não são informados sobre o estado de saúde do paciente em tempo integral, e só são informados quando o diagnóstico de ME já está concluído [10][11] .…”
Section: Resumo | Introduçãounclassified